(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. The vitamin D-receptor axis is involved in multiple physiological functions and altered states such as hypertension, mineral metabolism disorders, and inflammation. These disturbances are major risk factors for progression to end-stage kidney disease and cardiovascular disease. In addition, changes in internal systemic environment could be influencing the impact of survival in patients with kidney disease. This study aimed to evaluate the impact of vitamin D receptor (VDR) polymorphisms on hemodialysis patients’ survival. Material and Methods. A total of 122 hemodialysis patients and 120 healthy controls were compared for VDR gene polymorphism. Markers for full coverage in the VDR gene were selected and genotyped. The hemodialysis patients were followed until death event, which was considered the primary endpoint for the survival analysis. Results. Two tag SNPs (rs10875695 and rs11168293) showed significant differences between the hemodialysis and healthy patients. In survival analysis, the CC genotype for rs2248098, compared to the TT genotype, was associated with a worse mortality rate. After adjustments for age, sex, diabetes mellitus, and cardiovascular disease, the genotype CC (rs2248098) was associated with a higher risk of mortality in a multivariable analysis. Conclusions. Polymorphisms specific to patients with kidney disease could be influencing different conditions associated with mortality. Thus, these genetic markers, rs2248098 for example, would act in a specific time in the history of kidney disease and would bring different results of patient survival outcomes.